The Urgency of STEM Learning Approach in Improving Students' Creative Thinking and Collaboration Skills - Ichwan Zarkasi Brillyano Gunawan; Rina Sugiarti Dwi Gita; Kustiyowati (Postgraduate, University of Mataram, 2025)
This study analyzes the urgency of the STEM (Science, Technology, Engineering, and Mathematics) learning approach in improving students' creative thinking and collaboration skills. Using the Systematic Literature Review (SLR) method with PRISMA protocol for transparency, this study conducted a bibliometric analysis of 52 relevant international journal publications from Scopus. Data visualization, including network analysis using VOSviewer, showed that STEM is a highly concentrated central concept, indicating significant relevance and research interest. The creativity and 21st century skills nodes were consistently closely connected to STEM, with a trend of rapidly increasing attention through 2023. The high density of the words